Theoretical and experimental analysis of the oxidation of CO on Pt catalysts supported on modified TiO2(101) - Morgade, Cecilia Ines Nora (2015)
Abstract The dynamics of the CO adsorption on Pt nanoparticles deposited on TiO2(101) (pure, N-doped and/or reduced) have been investigated using UV-visible diffuse reflectance spectroscopy, diffuse reflectance infrared Fourier transform spectroscopy and density functional theory. The results point to that N-doping and oxygen vacancies in the Pt/N-TiO2 system should favor catalytic reactions in which CO conversion into CO2 takes place mediated by support surface O atoms.